The Impact of the Recruitment Process on Employee Performance - Firman, Ahmad; Inrawati, Nur (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
This study aimed to ascertain how the recruitment process at PT Triniaga Medika Makassar affected employee performance. The population of this research consisted of 182 employees and employees of PT Triniaga Medika Makassar. Using the Slovin formula, a basic random sampling technique was used to select the sample for this study. Each employee or employee had an equal chance of becoming a part of the sample. So that the total number of available samples is 65. The data source employed is primary data, i.e., data collected directly from respondents via questionnaire by researchers. The method of data analysis includes descriptive statistical analysis, tests of validity, reliability, normality, and testing of hypotheses via simple linear regression analysis, coefficient of determination test, and t test. This study indicates that the recruitment process at PT Triniaga Medika Makassar has a positive and significant impact on employee performance. This demonstrates that the implementation of recruitment, particularly at PT Triniaga Medika Makassar, has an effect on employee performance, such that the more effective the recruitment process, the higher the employee performance at PT Triniaga Medika Makassar.